Information and Communication Technology Usage among High School Teachers in Tehran, Iran. - Shahverdian, Nahid (2010)
Level of ICT usage may affect the rate of successful ICT implementation ineducation, and in the long run, the achievement of the goals of the fifth Iranian national socio-economic development program. The Iranian government has decided to offer ICT training courses for teachers to help them improve their ICT knowledge and skills. Thus, one of the most relevant objectives of this study was to determine the current level of ICT usage among high school teachers. This study had four main purposes: (a) To determine the level of ICT usage among high school teachers; (b) To determine the significant difference in ICT usage according to selected socio-demographic factors (gender, age, teaching experience, and subject taught); (c) To determine the level of perceived ease of use and perceived usefulness towards ICT usage among high school teachers; and (d) To identify barriers to the use of ICT among high school teachers. These issues were addressed using a self-administered survey questionnaire with a sample of high school teachers (n=395). Out of the 410 questionnaires, a total of 395 valid responses were returned. Data were analyzed using descriptive statistics, Analysis of Variance (ANOVA), and independent sample ttest. This study was conducted in 41 high schools located in two districts of Tehran. The finding of the study showed that the majority of high school teachers were categorized in low level ICT usage, and it accounted for 66.3% of the respondents. Results indicated that: (a) The level of ICT usage among high school teachers is low (b) there is significant difference in the mean score of ICT usage according to age and teaching experience while there is no significant difference in the mean score of ICT usage by the gender and subjects taught ;(c) the level of teachers’ perceived ease of use and usefulness is high ; (d) lack of time, lack of effective training, technical problems and inadequate access to resources are major barriers to ICT usage among high school teachers. The results showed that despite majority of teachers are in low level of ICT usage in their teaching but they have high level of perceived ease of use and usefulness. Participants indicated to have faced some problems when using ICT, and this needs to be given a serious consideration. Four major barriers such as lack of time, lack of effective training, technical problems and inadequate access to resources were identified. The present study proposed potential recommendations to teachers and Ministry of education to overcome these barriers.